Mapping challenges in developing sustainable small and medium industries: Integrating lean and green principles - Uly Amrina; Akhmad Hidayatno; Teuku Yuri M Zagloel (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This study explores the complexity of developing a sustainable small and medium industry (SMI) through a conceptual model that integrates lean and green manufacturing principles. Design/methodology/approach: This model includes a systems diagram that illustrates the structure of the interconnected variable and the interrelationships between goals, inputs, processes, and outputs required to achieve a system's goals by using both lean and green principles. The diagram uses causal loop diagram logic from systems thinking based on the literature review, multi-actor analysis, observations, and focus group discussions. Findings: Combining the efficiency benefits from lean principles and better environmental effectiveness from green principles would help to achieve sustainability. A conceptual structural map could support the integration processes by illustrating the variables, multi-actors, and multi-indicators required to achieve sustainability. Research limitations/implications: The conceptual model highlights the necessary linkage between lean and green practices that would help SMI researchers and decision-makers to navigate their activities in achieving sustainability. Originality/value: There is currently little discussion at the SMI level from a multi-actor perspective. The systems diagram offers a comprehensive picture that is the basis for further discussion of the complexity of integrating lean and green principles.
Keywords: 650; systems thinking; sustainability; lean; green; small and medium industry (SMI); cosmetics SMI